Contemporary financial management - McGuigan, James R. (South-Western College, 2001)
This book is divided into five parts: Introduction; Determinants of valuation; The capital investment decision; The cost of capital, Capital structure, and dividend policy; Working capital management and financial forecasting; Advanced topics in contemporary financial management.